Accountability And Financial Transparency Of Mosques Based On Sharia Enterprise Theory (Case Study Of Masjid Al-Muhajirin Desa Sidoraharjo) - lisdiawati, lisdiawati; Muchriana Muchran; Saida Said (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the accountability and transparency practices of financial management carried out by the administrators of the Al-Muhajirin Mosque, Sidoraharjo Village, South Sukamaju sub-district, North Luwu district. This research uses a qualitative approach based on interviews, observation and documentation. The data analysis technique used in this research is descriptive qualitative. The results of the research show that in its financial management, the Al-Muhajirin Mosque has done things that reflect responsibility (accountability) and openness (transparency) based on enterprise sharia theory, namely related to the awareness of the Mosque Committee/Manager that their duties are trust and worship of Allah. The management also realizes that reporting the mosque's financial accountability is not only to the community/congregation and donors but also to Allah SWT. Apart from that, mosque funds have been used for worship of Allah and there is nothing to cover up.